Experimental investigation on electrical resistivity of SFRC - Abad Zapico, Lucía (My University, 2015)
Reinforced concrete is widely used within the construction industry, being considered as the most important construction material as it combines the best properties of its components: tensile strength of steel and compressive strength of concrete at a relatively low cost compared with other materials. It is used in the construction of civil structures such as bridges or harbour piers, which need large amount of reinforcement making corrosion of steel one of the most critical parameters in assessing their service life. Lately, steel fibres have been used together with traditional reinforcement bars to limit the crack widths and minimize the chloride ingress to reduce the risk of pitting corrosion. To this extent, it seems that the use of steel fibres would be beneficial in larger constructions; however, there is also a concern that the decrease in resistivity caused by the conductivity of the fibres may increase the corrosion rate of the steel bars. This master thesis is divided in two different parts: resistivity studies and corrosion rate experiments. The first one aims to identify how steel fibres influence the resistivity of concrete and the second one to determine whether a measured low resistivity of steel fibre reinforced concrete could lead to increased corrosion rate of steel reinforcement bars. For the resistivity studies, the results show that resistivity was affected by numerous parameters among which moisture content should be highlighted, as it is the one with larger influence. It was determined that electrical resistivity of concrete decreases with increasing fibre contents and also that the orientation of fibres, something that is achieved by the pouring process, has an effect on the measured values. During the corrosion rate experiments, the galvanic current flowing through reinforcement bars was measured and with the help of Faraday’s law, the theoretical weight loss of those bars associated to the reduction of their crosssection was calculated. After comparing the different values in specimens with different fibre contents from three month’s chloride exposure, no significant evidence was found indicating that steel fibres may influence the corrosion rate of traditional reinforcement bars.
Keywords: Building Futures; Husbyggnad; Building Futures; Building Technologies